Prevention of economic crime as an important area of law enforcement authorities: state, trends, problems - Nipialidi, Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article examines the current state of economic crime on the basis of analysis of quantitative and qualitative indicators. The society of sustainable development to which Ukraine aspires is not possible without significant qualitative institutional changes in the political, legal, social and cultural, and especially economic spheres. Weakness and dysfunction of state institutions involved in the regulation and control of economic activity, provoked a significant surge in criminal redistribution and misappropriation of capital and resources, the spread and strengthening of bribery-sale relationship in public and private spheres, the formation of power-clan and corporate criminal communities of organized type.Combined with the manual management of law enforcement and judicial system, criminal and shady financial transactions were profitable kind of business and way of life for owners and managers of many businesses, which inevitably affected the state's economy and, consequently, the social sphere and led to an extreme degree of social tension and crisis of social institutions. Criminalization has affected almost all sectors of the economy: the banking sector, budget sphere, the fuel and energy sector, construction, land relations and corruption have become a link between them and the government.Analysing the current quantitative and qualitative indicators of economic crime in recent years, we came to the conclusion that in Ukraine there are negative trends in the prevention and combating of economic crimes. Although, according to official statistics, the share of economic crimes in the structure of crime in our country is only 6%, direct and indirect losses from them amount to billions of hryvnias annually.The state's European integration course, economic reforms and financial support of international organizations aimed at bringing the state economy out of crisis and improving the investment climate can be offset in the absence of a stable state institutional mechanism to combat economic crime, so the issue of prevention and prophylaxis of economic crime is and will remain extremely important.